Firm Heterogeneity in Skill Returns - Michael Johannes Böhm; Khalil Esmkhani; Giovanni Gallipoli (Institute of Labor Economics (IZA), 2023)
We quantify firm heterogeneity in skill returns and present direct evidence of worker–firm complementarities. Within a model of firms' demand for cognitive and noncognitive attributes we show that identification depends on the availability of skill measures. Linking administrative data to test scores we document worker sorting and convex earnings–skill relationships. We find that: (1) Both skills' returns vary substantially across employers and correlate weakly within-firm. (2) Workers with large endowments of a skill populate firms with higher returns to it. Sorting intensifies with the cross-sectional dispersion of returns. (3) Complementarities and sorting significantly influence the earnings distribution.
Keywords: D3; J23; J24; J31; 330; firm heterogeneity; skill return; sorting; earnings distribution